IMPROVING TEACHERS' PEDAGOGIC COMPETENCE TO IMPLEMENT PROBLEM BASED LEARNING THROUGH PEER TEACHING - Hilmi Helen (Laboratorium Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Riau, 2021)
The teacher profession is very crucial in learning since it trains students to have abilities and skills as well as good attitudes in life. A competent teacher is certainly a reflection of continuous training and experience. One way to hone teachers’ competence in teaching is through peer teaching. Through this method, it is hoped that the teacher will have competence in teaching. Particularly, in this study the focus was peer teaching on the problem-based learning model in which students were trained to solve problems based on the problems presented by the teacher. This research was conducted in October 2019 at SMP Negeri 11 Dumai with 22 teachers as the research subjects. The instrument was the observation sheet used to record teachers’ activity in the classroom. The results showed that the teachers’ pedagogical competence in cycle I was 71.15 with Sufficient category and it increased in cycle II to 81.09 with Good category. Based on the results of this study, it could be concluded that the teachers’competence to implement problem based learning has increased through peer teaching method.